Inhabiting Space in Digital City Models. Exploring Immersive Design in Futuristic Digital Environments - García Ladrón de Guevara, Juana María; Roig Segovia, Eduardo; Del Blanco García, Federico Luis (European Public & Social Innovation Review, 2025)
Introduction: Nowadays we find numerous virtual environments that challenge the limits of the imagination. An example of this challenge is the video game Cyberpunk 2077, whose scenario recreates a futuristic environment based on a vertical distribution scheme. In contrast to the horizontal distribution schemes that we normally observe in open-world digital environments, a new field of analysis opens up on how high-rise virtual cities are shaped and designed. Objective: The aim of the research is to extract and understand the design keys that allow the space to be experienced in the most dynamic and immersive way possible in these virtual spaces. Methodology: The methodology uses the case method and seeks to defragment the design codes that make up this digital city, extrapolating them to the physical experience of real architecture. Results: By decomposing the video game and its contents, a whole mapping of information is extracted that allows us to understand the established design links. Discussion: It is observed how the visual language graphed in plan is insufficient to understand the multiplicity of levels that the futuristic city presents, being relevant presence of the elevation when it comes to understanding the space and the magnitude of its interconnections.